Introduction: â€œWho Cares for the Carers?â€: A Feminist Approach to Ecological Citizenship - Pal, Dipanwita (Journal of Ecohumanism, 2024)
This special issue has chiefly four components to focus uponâ€”citizenship, ecological responsibilities, ecofeminist approach and politics of care, among whom the primary component is citizenship. The recent discourse on citizenship is domineered by the liberal and the civic republican frameworks. T. H. Marshall defines citizenship as â€œa status bestowed on those who are full members of a communityâ€ (1950, 14). Disparagingly, some other critics cite Aristotleâ€™s definition of a citizen as one who â€œshares in decision and officeâ€ with the capacity â€œto rule and be ruled finelyâ€ (1984, 87, 91). Teena Gabrielson sums up this issue with the explanation: â€œâ€¦ the liberal model emphasizes citizenship as a public status that ensures the holder of civil, political and social rights; while the civic republican model, renewed by the communitarian challenge to liberalism, emphasizes the public duties, virtues and practices of citizenshipâ€ (2008, 430).